MUNĀSABAH: UNDERSTANDING, POSTULATE, METHOD OF DISCOVERY, DISTRIBUTION AND APPLICATION IN THE INTERPRETATION OF QUR’AN - Sumanto Sumanto (Hunafa: Jurnal Studia Islamika, 2018)
Mannā’ al-Qaṭṭān in his book, Mabāḥiṡ fī ‘Ulūm al-Qur`ān, explains munasabah which muqarabah is also musyakalah (likeness). It means between verses with other verses have relationships and likenesses, so they are interrelated and mutual need, closely related to the science of causality which is a causal relationship that cannot stand alone without the help of the meaning of the verse before or after. Majority of Islamic scholar have agreed that the sequence of verses in a single surah is a sequence of tauqīfī, the order that has been determined by the Prophet Muhammad as the recipient of revelation. However, they disagree about the sequence of the surah in the muṣḥaf, whether it is tauqīfī or taufīqī̄ (sorting by the ijtihād of the compilers of the muṣḥaf). Developing the supposition that the Qur’anic themes lose relevance between one part and the other. Knowing or connecting between parts of the Qur’an, either between sentences or between verses and surah, thereby deepening the knowledge and the introduction of the Qur’an and reinforcing belief in revelation and miracles.